A computer simulation to investigate the association between gene-based gifting and pair-bonding in early hominins. Issue 116 (March 2018) - Rouly, Ovi Chris
Abstract: This article describes simulation research based on the Hamiltonian theory of gene-based altruism. It investigates the origin of semipermanent breeding bonds during hominin evolution. The research framework is based on a biologically detailed, ecologically situated, multi-agent microsimulation of emergent sociality. The research question tested is whether semipermanent breeding bonds (an emergent homoplastic social construct) might emerge among primate-like agents as the consequence of a mutation capable of supporting involuntary prosocial behavior. The research protocol compared several, single independent-variable longitudinal studies wherein hundreds of generations of autonomous, initially promiscuous, biologically detailed, hominin-like artificial life software agents were born, allowed to forage, reproduce, and die during experimental intervals lasting several simulated millennia. The temporal setting of the experiment was roughly contemporaneous with, or slightly after the time of, the Pan-Homo split. The simulation investigated what would happen if, within a population, a single gene for prosocial behavior (the independent variable in the experiment) was either switched on or switched-off. The null hypothesis predicted that, if the gene was switched off, then semipermanent breeding bonds (the dependent variable) would nonetheless emerge within the population. The results of the simulation rejected this null hypothesis, by showing that semipermanent breeding bonds would reliably emerge among the experimental populations but not among the control groups. Moreover, it was found that, across all experimental settings having constrained population numbers, the portion of each population having no prosocial trait would die out early, whereas the portion with the prosocial trait would survive. Large control populations had no discernible loss. The results of this research imply that, during the early stages of hominin evolution, there might have been a set of initially gene-based, altruistic excess forage-sharing social traits that contributed to the onset of morphological and additional complex social changes characteristic of this group. This work also demonstrates that modern computational technologies can extend our ability to test 'what if' hypotheses appropriate to the study of early hominin evolution.